Form-fit joining of hybrid busbars using a flexible tool demonstrator - Reichel, A. (2021)
This paper is focused on hybrid busbars made from copper and aluminum strips and presents a flexible tool demonstrator capable of replicating material flow in the lancing, bending and compression stages of a new joining by forming process without auxiliary elements. The flexible tool demonstrator is defined by its modular concept that allows the active tool components to be easily interchanged for testing and exploring different materials and thickness combinations, surface conditions and cross-section areas of the strips under laboratory conditions. Experimental and numerical simulation with a selected hybrid busbar geometry validates the overall concept and fabrication of the demonstrator and shows that the new joining by forming process can produce permanent form-fit joints with smooth upper and lower surfaces containing all the plastically deformed material within the thickness of the two strips. Complete filling of the free volume left in-between the thickness of the two strips allows obtaining an electric resistance lower than that of fastened hybrid busbars.